Guidelines for G-quadruplexes: I. In vitro characterization - Luo, Yu; Granzhan, Anton; Marquevielle, Julien; Cucchiarini, Anne; Lacroix, Laurent; Amrane, Samir; Verga, Daniela; Mergny, Jean-Louis (Biochimie, 2023)
Besides the well-known DNA double-helix, non-canonical nucleic acid structures regulate crucial biological activities. Among these oddities, guanine-rich DNA sequences can form unusual four-stranded secondary structures called G-quadruplexes (G4s). G4-prone sequences have been found in the genomes of most species, and G4s play important roles in essential processes such as transcription, replication, genome integrity and epigenetic regulation. Here, we present a short overview of G-quadruplexes followed by a detailed description of the biophysical and biochemical methods used to characterize G4s in vitro. The principles, experimental details and possible shortcomings of each method are discussed to provide a comprehensive view of the techniques used to study these structures. We aim to provide a set of guidelines for standardizing research on G-quadruplexes; these guidelines are not meant to be a dogmatic set of rules, but should rather provide useful information on the methods currently used to study these fascinating motifs.
Keywords: epigeneze genetická; Nucleic acids; G-Quadruplexes; G-kvadruplexy; genom; DNA; Epigenesis, Genetic; G-quadruplexes; Quadruplex ligand; Structure determination; Genome; Spectroscopy